Training on Solar Cell Technology as a Solar Power Plant in Graha Citra Mas Housing Estate Kaliwates, Jember - Muhammad Nurkoyim; Nasrul Ilminnafik; Muhammad Dimyati Nashrullah; Muhammad Izzuddin Al Haq (RESPINARIA : Jurnal Pengabdian Kepada Masyarakat, 2024)
Energy needs are increasing but on the other hand the availability of petroleum reserves as conventional energy is running low, this forces humans to look for alternatives to energy. Indonesia as a country with a relatively good tropical climate in the duration of the sun shines. This matter is a potential to answer the need for alternative energy to replace petroleum, namely solar light or the sun. By utilizing solar panels, solar cells simply consist of a connection of p and n type semiconductor materials which when exposed to sunlight will occur electron flow, from this flow is referred to as electricity or converting solar radiation into electricity. In an effort to educate and serve a number of lecturers from the Department of Mechanical Engineering, University of Jember, held a service located in RT 04 / RW021 Graha Citra Mas Housing, Tegal Besar Village, Kaliwates District, Jember Regency, with the aim of understanding the community regarding Solar Cell Technology as a Solar Power Plant (PLTS). The service runs with the delivery of material and continued by emphasizing discussion and question and answer. With the results of the service felt illustrated and enlightened from the material and answers that the speaker conveyed.